2020
DOI: 10.1096/fj.202000289r
|View full text |Cite
|
Sign up to set email alerts
|

An immune response to the avascular lens following wounding of the cornea involves ciliary zonule fibrils

Abstract: The lens and central cornea are avascular. It was assumed that the adult lens had no source of immune cells and that the basement membrane capsule surrounding the lens was a barrier to immune cell migration. Yet, microfibril‐associated protein‐1 (MAGP1)‐rich ciliary zonules that originate from the vasculature‐rich ciliary body and extend along the surface of the lens capsule, form a potential conduit for immune cells to the lens. In response to cornea debridement wounding, we find increased expression of MAGP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 83 publications
1
49
0
Order By: Relevance
“…In our studies with the developing chick embryo eye, which unlike mammalian embryo eyes has no lens‐associated tunica vasculosa that could serve as a vascular source of lens resident immune cells, we show that the ciliary zonules between the ciliary body and the lens are the likely path by which immune cells populate the lens during development. Since we previously show that immune cells that surveille the lens in response to corneal wounding are able to migrate across the lens basement membrane capsule, 21 we expect that immune cells use this same path to take residence in the lens during development. We also suggest that this is the pathway by which resident immune cells repopulate the lens in the adult as the vasculature of the tunica vasculosa of mammals is removed by apoptosis prior to birth 56 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our studies with the developing chick embryo eye, which unlike mammalian embryo eyes has no lens‐associated tunica vasculosa that could serve as a vascular source of lens resident immune cells, we show that the ciliary zonules between the ciliary body and the lens are the likely path by which immune cells populate the lens during development. Since we previously show that immune cells that surveille the lens in response to corneal wounding are able to migrate across the lens basement membrane capsule, 21 we expect that immune cells use this same path to take residence in the lens during development. We also suggest that this is the pathway by which resident immune cells repopulate the lens in the adult as the vasculature of the tunica vasculosa of mammals is removed by apoptosis prior to birth 56 .…”
Section: Discussionmentioning
confidence: 96%
“…Whether injury activated resident immune cells integrated among the lens epithelium are responsible for contributing to the production of pro‐inflammatory factors and chemokines is not yet known. Lens resident immune cells provide a potential mechanism to recruit circulating innate immune cells to the lens as has been shown to occur in response to lens dysgenesis caused by conditional deletion of N‐cadherin, corneal wounding, and cataract surgery 20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…68 Immune cells, known to populate the vascularized uveal tract of the eye, which includes the iris, ciliary body, and choroid, 73 have been proposed to surveille the lens by migrating across the ciliary zonules. 68,74 Further studies are underway to determine the ocular source and trafficking route of macrophage-like cells found in the Trpm3-MM mutant lens.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of cooperative immune responses in the eye was also provided by studies revealing that surveillance of the lens by immune cells is induced in response to debridement wounding of the cornea [163]. In these studies, it was discovered that within one day of cornea wounding, immune cells sourced in the ciliary body are induced to travel along the ciliary zonules and populate the lens anterior surface from where they migrate across the lens capsule (Figure 3) [163].…”
Section: Surveillance Of the Lens By Immune Cells In Response To Eye Injurymentioning
confidence: 98%
“…The fact that the eye is considered an immune privileged site, and that the lens is avascular [160] and surrounded by a thick matrix capsule [161], had led investigators to presume that immune cells would not be associated with or recruited to wounded or dysgenic lenses, even though non-canonical mechanisms of immune cell recruitment had been discovered for other avascular regions of the eye [65,162]. It is only recently that it has been shown that there is surveillance of the lens by immune cells in response to eye injury, an adaptive immune response to lens degeneration, and a repair response by immune cells activated upon lens wounding [163][164][165]. These studies also provided evidence that the association of immune cells with the lens has negative outcomes, including a role for immune cells in lens fibrosis [164,165].…”
Section: Protective and Reparative Immune Responses To Wounding In The Lens And Their Links To Fibrosismentioning
confidence: 99%